2007
DOI: 10.1074/jbc.m611559200
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a Dominant Negative Functional Domain on DAPK-1 That Degrades DAPK-1 Protein and Stimulates TNFR-1-mediated Apoptosis

Abstract: DAPK-1 is a stress-activated tumor suppressor protein that plays a role in both proapoptotic or antiapoptotic signal transduction pathways. To define mechanisms of DAPK-1 protein regulation, we have determined that DAPK-1 protein has a long half-life, and therefore its activity is primarily regulated at the protein level. Changes in DAPK-1 protein levels occur by a cathepsin B-dependent pathway, prompting us to evaluate whether cathepsin B plays positive or negative role in DAPK-1 function. The transfection of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
39
0

Year Published

2008
2008
2013
2013

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 35 publications
(45 citation statements)
references
References 53 publications
6
39
0
Order By: Relevance
“…In agreement with our observations, recent studies suggest that DAPK has a role in maintaining cellular homeostasis and promoting cell survival under normal cell growth conditions (37)(38)(39)(40). Moreover, we and others have demonstrated previously that TNF␣ treatment results in DAPK degradation and sensitization of cells to apoptosis (29,41), whereas siRNA-mediated knockdown of DAPK enhanced TNF␣-induced apoptosis (29,41). These studies confirm a role for DAPK as a survival factor in the TNF␣ signaling pathway.…”
Section: Discussionsupporting
confidence: 66%
See 1 more Smart Citation
“…In agreement with our observations, recent studies suggest that DAPK has a role in maintaining cellular homeostasis and promoting cell survival under normal cell growth conditions (37)(38)(39)(40). Moreover, we and others have demonstrated previously that TNF␣ treatment results in DAPK degradation and sensitization of cells to apoptosis (29,41), whereas siRNA-mediated knockdown of DAPK enhanced TNF␣-induced apoptosis (29,41). These studies confirm a role for DAPK as a survival factor in the TNF␣ signaling pathway.…”
Section: Discussionsupporting
confidence: 66%
“…HA-tagged DAPK-WT, ⌬CAM, and K42A vectors were a gift of Adi Kimchi (Weizmann Institute). For the generation of HA-tagged DAPK deletion mutants, stop codons were introduced, as described previously (29). FLAG-tagged TSC2 was a gift from Andrew Tee (University of Cardiff).…”
Section: Methodsmentioning
confidence: 99%
“…Previous studies have shown activation of DAPK (via dephosphorylation of p-S308) leads to enhanced degradation by the proteasome (3, 10, 11) and lysosome (6). To distinguish between proteasomal and lysosomal degradation, we induced the expression of B␣ or B␦ in HEK-T-Rex cells and then treated the cells with 10 M MG132 or 100 M chloroquine for 6 h. Cells treated with proteasomal inhibitor MG132 could rescue the B␣-or B␦-induced decrease in DAPK protein levels, whereas the lysosomal inhibitor could not (Fig.…”
Section: Pp2a-b␣ and Pp2a-b␦ Holoenzymes Associate With Dapk-mentioning
confidence: 99%
“…However, a number of cellular studies have shown that DAPK-1 can exhibit diverse biological functions that include the following: interferon-induced cell death (16); amino acid starvation-linked autophagy and membrane blebbing (17); integrin inhibition and cell detachment (18); ERK 4 -dependent apoptosis (10,15); oncogene activation of p53 (11); induction of phosphorylation within the p53 transactivation domain (19); and genetic tumor suppressor functions (20). Furthermore, although DAPK-1 can function as a growth suppressor (21), growing evidence also indicates it can function as an anti-apoptotic factor (22)(23)(24)(25) suggesting that DAPK-1 can respond to different input signals catalyzing distinct effects on cell growth.…”
mentioning
confidence: 99%